ANALYSIS OF STUDENT LEARNING INTERESTS IN CHEMISTRY CLASS XI IPA AT A PANYIPATAN PRIVATE SENIOR HIGH SCHOOL - Rahmah; Novi Rahmawanti; Novrian Dony (CV. ADIBA AISHA AMIRA, 2023)
This study aims to describe the profile of students' interest and the factors that influence students' interest in learning chemistry in class XI IPA SMAS Abdul Kadir Panyipatan. This type of research is a qualitative descriptive research with a phenomenological approach. Data collection techniques were carried out through interviews, direct learning activities carried out by researchers, questionnaires, and document studies. The number of samples 15 students, was carried out using a census technique by taking the entire population of class XI IPA students. The results showed that the profile of students' interest in studying chemistry in class XI IPA at Abdul Kadir Panyipatan Private High School was 20% high, 33.3% medium, and 46.7% low. The factors that influence the learning interest of class XI IPA students consist of internal factors which include curiosity, initial ability, perception, intelligence, aspirations, and motivation. Internal factors include teachers, learning models, teaching materials, and peers